2021
DOI: 10.3390/genes12020236
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis TETRATRICOPEPTIDE THIOREDOXIN-LIKE 1 Gene Is Involved in Anisotropic Root Growth during Osmotic Stress Adaptation

Abstract: Mutations in the Arabidopsis TETRATRICOPEPTIDE THIOREDOXIN-LIKE 1 (TTL1) gene cause reduced tolerance to osmotic stress evidenced by an arrest in root growth and root swelling, which makes it an interesting model to explore how root growth is controlled under stress conditions. We found that osmotic stress reduced the growth rate of the primary root by inhibiting the cell elongation in the elongation zone followed by a reduction in the number of cortical cells in the proximal meristem. We then studied the stif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 70 publications
(138 reference statements)
2
7
0
Order By: Relevance
“…A fruitful aspect discussed in the work involves the issue of the impact of the FLA4-FEI pathway on agronomic traits, such as improving plant resistance to several abiotic and biotic stresses in multiple crops. In line with this, as reported in this issue by Cuadrado-Pedetti et al [3], drought conditions cause stress to the plant, and the plant will try to adapt to these conditions. A large number of genes have been identified that allow plants to face these conditions; several of these genes have a function in root development.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…A fruitful aspect discussed in the work involves the issue of the impact of the FLA4-FEI pathway on agronomic traits, such as improving plant resistance to several abiotic and biotic stresses in multiple crops. In line with this, as reported in this issue by Cuadrado-Pedetti et al [3], drought conditions cause stress to the plant, and the plant will try to adapt to these conditions. A large number of genes have been identified that allow plants to face these conditions; several of these genes have a function in root development.…”
supporting
confidence: 79%
“…Developmental processes can influence CWs, but also CWs can affect plant development. In this issue, two reviews [1,2] and a research paper [3] studied these aspects. In the work of Cruz-Valderrama et al, 2021, authors reviewed what is known about the importance of the CW during flower development [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…AtGASA1, the homolog of PeuGASA15, has been reported to weakly interact with VIT by phage display technology [60]. VIT, also named TETRATRICOPEPTIDE-REPEAT THIOREDOXIN-LIKE 1 (TTL3), plays an important role in brassinosteroid and auxin signaling, and is required for osmotic stress tolerance [60][61][62][63][64][65]. Consistent with Arabidopsis, IAA induced PeuGASA15 expression and mannitol significantly inhibited PeuGASA15 expression in the leaves of pGASA15: GUS transgenic leaves (Figure 11).…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, from the 12 DEG GmTrx , GmTrx92 was exclusively regulated, specifically down-regulated, at the translational level ( Figure 4 b; Table 1 ). This protein had high homology with Arabidopsis TTL1 ( Supplementary Figure S2 ) for which a role in the root adaptation during osmotic stress is suggested [ 76 ]. It is worth noting that four out of five soybean nucleoredoxins were DEGs in nodulated and water-restricted plants; specifically, they were up-regulated at the TOTAL+PAR level in the N+WR vs. N+WW contrast ( Figure 4 b; Table 1 ).…”
Section: Discussionmentioning
confidence: 99%